Implementation and evaluation of a novel, unofficial, trainee-organized hospital addiction medicine consultation service. Issue 4 (October 2021) - Brothers, Thomas D.; Fraser, John; MacAdam, Emily; Morgan, Brendan; Francheville, Jordan; Nidumolu, Aditya; Cheung, Christopher; Hickcox, Samuel; Saunders, David; O'Donnell, Tiffany; Genge, Leah; Webster, Duncan
Background: To evaluate a novel, unofficial, trainee-organized, hospital addiction medicine consultation service (AMCS), we aimed to assess whether it was (1) acceptable to hospital providers and patients, (2) feasible to organize and deliver, and (3) impacted patient care. Methods: We performed a retrospective descriptive study of all AMCS consultations over the first 16 months. We determined acceptability via the number of referrals received from admitting services, and the proportion of referred patients who consented to consultation. We evaluated feasibility via continuation/growth of the service over time, and the proportion of referrals successfully completed before hospital discharge. As most referrals related to opioid use disorder, we determined impact through the proportion of eligible patients offered and initiated on opioid agonist therapy (OAT) in hospital, and the proportion of patients who filled their outpatient prescription or attended their first visit with their outpatient OAT prescriber. Results: The unofficial AMCS grew to involve six hospital-based residents and five supervising community-based addiction physicians. The service received 59 referrals, primarily related to injection opioid use, for 50 unique patients from 12 different admitting services. 90% of patients were seen before discharge, and 98% agreed to addiction medicine consultation. Among 34 patients with active moderate-severe opioid use disorder who were not already on OAT, 82% initiated OAT in hospital and 89% of these patients continued after discharge. Conclusions: Established in response to identified gaps in patient care and learning opportunities, a novel, unofficial, trainee-organized AMCS was acceptable, feasible, and positively impacted patient care over the first 16 months. This trainee-organized, unofficial AMCS could be used as a model for other hospitals that do not yet have an official AMCS.